Antecedents to the creation of 'Thai Select Unique' restaurant brand equity - Sornsaruht, Puris (My University, 2020)
Thai cuisine is world renowned for its savoury flavours and the variety of its potential presentations. Consistently, Thai dishes have been at the top of international surveys for its quality, with the Thai government now supporting multiple programs to promote Thai food under the Thai Select branding campaign for use with restaurants. Therefore, the authors chose to investigate how diners perceived their local authentic food experience from restaurants, which had been awarded the Thai Select Unique (TSU) certification. From a potential population of 50 restaurants, ten TSU restaurants were randomly selected for a survey of diners concerning their opinions on how online advertising strategy (OA), their perceived quality (PQ), their brand awareness (BA), and brand loyalty (BL) played a role in the restaurant's overall brand equity (BE). From the conceptualized eight hypotheses, a preliminary confirmatory factor analysis (CFA) and goodness-of-fit (GoF) analysis was conducted, followed by structural equation modelling (SEM) using LISREL 9.1 on the item statements from the questionnaires obtained from 415 TSU diners. Results revealed that all the causal variables in the model had a positive effect on BE, which can be explained by the combined influence of the factors (R2) being 93%. Furthermore, ranked in importance, OA, BA, BL, and PQ with total effects of 0.96, 0.88, 0.56 and 0.09, respectively. This study is also original and timely as it details how social media (SM) has become the foundation for what the authors have identified as 'selfie tourism' in the development of a destination's brand equity.
Keywords: Brand awareness; Brand loyalty; Cuisine; Culinary art; Selfie tourism